2011
DOI: 10.2337/dc10-2115
|View full text |Cite|
|
Sign up to set email alerts
|

One-Year Results of a Community-Based Translation of the Diabetes Prevention Program

Abstract: OBJECTIVEAlthough the Diabetes Prevention Program (DPP) and the Finnish Diabetes Prevention Study (FDPS) demonstrated that weight loss from lifestyle change reduces type 2 diabetes incidence in patients with prediabetes, the translation into community settings has been difficult. The objective of this study is to report the first-year results of a community-based translation of the DPP lifestyle weight loss (LWL) intervention on fasting glucose, insulin resistance, and adiposity.RESEARCH DESIGN AND METHODSWe r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
219
1
10

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(235 citation statements)
references
References 24 publications
5
219
1
10
Order By: Relevance
“…Trial Registration: NCT00631345; Clinicaltrials. gov, registered March 5, 2008 IRB: Wake Forest University Health Sciences; IRB00000613; initial approval 10/10/2006 the broader population [3][4][5][6][7][8][9][10][11][12]. According to a recent meta-analysis of 22 DPP translational studies, these programs have achieved modest success with an average 12-month weight loss of 2.32 kg [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Trial Registration: NCT00631345; Clinicaltrials. gov, registered March 5, 2008 IRB: Wake Forest University Health Sciences; IRB00000613; initial approval 10/10/2006 the broader population [3][4][5][6][7][8][9][10][11][12]. According to a recent meta-analysis of 22 DPP translational studies, these programs have achieved modest success with an average 12-month weight loss of 2.32 kg [13].…”
Section: Discussionmentioning
confidence: 99%
“…The Healthy Living Partnerships to Prevent Diabetes (HELP PD) trial was one of the largest randomized controlled trials to translate the methods of the original DPP [14]. Previously we have shown that the HELP PD intervention was effective in reducing fasting glucose relative to an enhanced usual care condition [9,10]. We also reported that the intervention could be done at a lower cost than the DPP intervention [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 16 studies reviewed, investigators noted that significant reductions in hemoglobin A1C values were reported in eight studies. A recent review of literature published in 2011 and 2012 assessing the evidence emerging from community-based participatory research approaches involving CHWs provided evidence of improved glycemic control or reduced risk of disease progression (2,3,7,19,43,60,61,111,116,127). Cancer screening.…”
Section: Evidence For Community Health Worker Effectiveness In the Unmentioning
confidence: 99%
“…These include goal-setting, action-planning, self-monitoring, progress feedback, problem-solving, and reviewing goals. Group-based interventions have been shown to be effective for diabetes prevention, self-management and support, providing an environment that facilitates peer discussions about problems and personal experiences, resulting in significant benefits, including weight loss, improved fasting glucose levels, improved energy, and improved emotional state (Katula et al, 2011;Trento et al, 2010;Holma et al, 2008).…”
Section: Study Setting: Living Well Taking Control Programme Structumentioning
confidence: 99%